HPV16 L1 and L2 DNA methylation predicts high‐grade cervical intraepithelial neoplasia in women with mildly abnormal cervical cytology. Issue 3 (7th March 2013) - Lorincz, Attila T; Brentnall, Adam R; Vasiljević, Nataša; Scibior‐Bentkowska, Dorota; Castanon, Alejandra; Fiander, Alison; Powell, Ned; Tristram, Amanda; Cuzick, Jack; Sasieni, Peter
<x xml:space="preserve">Abstract</x> DNA methylation changes in human papillomavirus type 16 (HPV16) DNA are common and might be important for identifying women at increased risk of cervical cancer. Using recently published data from Costa Rica we developed a classification score to differentiate women with cervical intraepithelial neoplasia grade 2 or 3 (CIN2/3) from those with no evident high‐grade lesions. Here, we aim to investigate the performance of the score using data from the UK. Exfoliated cervical cells at baseline and 6‐months follow‐up were analyzed in 84 women selected from a randomized clinical trial of women undergoing surveillance for low‐grade cytology. Selection of women for the methylation study was based on detectable HPV16 in the baseline sample. Purified DNA was bisulfite converted, amplified and pyrosequenced at selected CpG sites in the viral genome (URR, E6, L1 and L2), with blinding of laboratory personnel to the clinical data. The primary measure was a predefined score combining the mean methylation in L1 and any methylation in L2. At the second follow‐up visit, 73/84 (87%) women were HPV16 positive and of these 25 had a histopathological diagnosis of CIN2/3. The score was significantly associated with CIN2/3 (area under curve = 0.74, p = 0.002). For a cutoff with 92% sensitivity, colposcopy could have been avoided in 40% (95% CI 27–54%) of HPV16 positive women without CIN2/3; positive predictive value was 44% (32–58%) and negative predictive value was 90% (71–97%). We conclude that quantitative DNA methylation assays could help to improve triage among HPV16 positive women.